Penatalaksanaan Holistik Pada Perempuan Usia 65 Tahun Dengan Hypertensive Heart Disease (HHD) dan Dislipidemia Melalui Pendekatan Kedokteran Keluarga - Akmal, Vina Amelia; Angraini, Dian Isti (Medula, 2024)
Hypertensive heart disease (HHD) is a term applied to refer to heart disease as a whole, starting from left ventricular hypertrophy (LVH), cardiac arrhythmias, coronary heart disease, and chronic heart disease, which are caused by increased blood pressure, either directly or indirectly. The number of patients with Hypertensive Heart Disease (HHD) is not known with certainty, but in several studies it is stated that people with hypertension will develop heart disease. Often patients fail in treatment because of their inability to modify their lifestyle, so doctors must treat patients holistically from various aspects. Application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient-centered and family problem-solving framework. The study conducted was a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from patient medical records. Patient Mrs. S, 65 years old, came with complaints that discomfort when breathing and frequent palpitations. Known to suffer from hypertension since 18 years ago and a history of hospitalization due to a previous heart disease. The patient had been taking antihypertensive medication but stopped it because he felt he was fine. The patient is worried that the complaint will worsen and interfere with activities. The patient was clinically diagnosed with HHD. Furthermore, management, intervention and evaluation are carried out. The diagnosis and management of these patients has been carried out holistically, patient centered, family approach and community oriented based on several recent theories and research. In the process of behavior change, the patient has reached the trial stage.